Demplot Aplikasi Usahatani Ekologis Terpadu Pada Tanah Tegakan Kelapa Di Desa Lendang Nangka Utara Masbagik Lombok Timur Nusa Tenggara Barat - I Ketut Ngawit; Wayan Wangiyana; Ni Made Laksmi Ernawati; Ni Wayan Sri Suliartini (Jurnal Gema Ngabdi, 2026)
The implementation of this demonstration field aims to improve the knowledge and skills of farmers in the management of coconut plantations through the application of integrated ecological agriculture carried out on coconut plots by intensively cultivating various types of annual vegetable crops. The activities of the demonstration plots and accompaniment proceeded safely, smoothly, and pleasantly. It has been shown that the initially low level of participation and enthusiasm of the participants was able to increase after taking part in all successive accompaniment and demonstration activities. There is an increase in the knowledge and skills of farmers participating in demonstration plots to manage the soil of coconut plantations through the application of an integrated ecological land management system with intensive tillage, the use of organic fertilizer, and the cultivation of vegetable crops following a cycle and series planting pattern. Intensive management of coconut palm soils, in which several vegetable crops are cultivated, leads to improved growth and yield performance of the coconut palms, thereby increasing the farmers' profit and thus their income. The profit and income of farmers from growing mustard pak choy, red onions, chili, and tomatoes on coconut plantation areas is higher compared to growing long beans, red chili, sweet corn, and spinach. It is recommended to plant pak choi, small chili peppers, tomatoes, and shallots on the ground under coconut palms, using a cycle and row planting system and an application of organic fertilizer at a dose of 20-25 tons ha-1, supplemented with NPK Ponska 100-150 kg ha-1